The Player, The Game, and The Jutsu: Measuring Mechanical Experiences of Gameplay - Soraine, Sasha (My University, 2024)
Research on game-related experiences centres player experiences (PX). However, our understanding of PX is limited. At a definitional level, there is no consensus on the dimensions of PX, its proposed constructs overlap in scope, and their specific relationships to game design decisions can be unclear. At a functional level, PX focuses on a narrow set of positive, optimal experiences, even though negative experiences and spectator experiences are also fundamentally important to understanding games. We synthesize various works into the Experiential Tetrad (ExperT) — a perspective-dependent theoretical framework for all game-related experiences. ExperT proposes that holistic experiences are the combination of four interrelated experiential types (mechanical, emotional, aesthetic, and socio-cultural) which are clearly scoped to specific game elements, and timescale oriented. ExperT highlights how the user perspective (e.g. player, spectator) influences the overall experience by changing its characterising experiential type. PX is grounded during play, and so it is heavily characterised by mechanical experiences. Spectator experiences (SX) are grounded out of play, and so are heavily characterised by socio-cultural experiences. Our work explores mechanical experiences (MX) through a player lens, with the goal of modeling and measuring it. We define MX as the relationship between the player’s abilities and the game’s challenges. We scope our work to focus on two qualities of MX: mechanical achievability (can the player complete the challenge?) and mechanical difficulty (how design decisions affect the mechanical achievability). This exploration results in jutsus — a knowledge capture artifact that visualizes the MX of a challenge for a particular player. Jutsus connect the challenge’s design to the MX, and so could be a useful tool for designers and researchers in understanding a part of PX. To arrive at jutsus, we construct: a Player Model, that describes players by their ability proficiencies (represented as a player profile); a Challenge Model, that describes gameplay challenges by their ability requirements (represented as a competency profile); and, a process of comparing player profiles and competency profiles to quantify their MX. This thesis adds to the fundamental science of games user research (GUR) and human computer interaction (HCI). It establishes a new theory and opens up new avenues of future work in experience modeling.
Mechanics of Jutsus
Keywords: video games; human computer interaction; games user research; mechanical experiences; jutsus; player experience